Overview Of Gender Victims Of Family In The Household In Garut District - Hanifah, Hanifah; Rafiudin, Rafiudin; Madaniyyah, Fathimah; Supiana, Supiana (International Journal of Islamic Khazanah, 2020)
Data from the West Java Women's and Child Empowerment (P2TP2A) Integrated Service Center counselor, shows that the number of domestic violence (KDRT) in West Java is still high. In one year P2TP2A can handle more than 100 cases. that number could be more because until now there are still many victims of domestic violence who do not dare to report. This is a concern of the community and the regional government of West Java, so the problem is how to protect victims of domestic violence in Garut. This writing study uses literature studies that emphasize data collection through searching / reviewing books related to research. The data analysis method used is a descriptive-analytical method by collecting and compiling data, then analysis and interpretation of the data are sought. Violence against women and children victims of domestic violence in Garut Regency over the past five years as many as 430 cases including 2014 violence against women, 46 cases, in 2015 there were 31 cases, in 2016 there were 37 cases, in 2017 there were 30 cases and in 2018 as many as 17 cases. This shows that the amount of violence against women has decreased from year to year. Garut Regency protects women and children who are victims of violence by fulfilling the rights of women and children victims of violence and discrimination starting from prevention efforts, social services, and rehabilitation. All protection aims to protect women and provide security in the fulfillment of their rights by providing consistent and systematic attention aimed at achieving gender equality.